Changes in macrophytes and fish communities in the cooler of Ignalina nuclear power plant (1988–2008) - Marčiulionienė, Danutė; Montvydienė, Danguolė; Kazlauskienė, Nijolė; Kesminas, Vytautas (Journal of Environmental Engineering and Landscape Management, 2011)
On the basis of long-term studies of the radionuclide and heavy metals accumulation and scatter in biotic and abiotic components of Drūkšiai Lake as well as of water and bottom sediments toxicity and genotoxicity, radioactive, chemical and thermal pollution potential impacts on macrophytes and fish communities of Drūkšiai Lake were evaluated. Before starting exploitation of Ignalina Nuclear Power Plant (INPP) 95 species of macrophytes were found in Drūkšiai Lake. Since the start-up of the second nuclear reactor of INPP (1987), significant alternations in macrophytes species composition and biomass in Drūkšiai Lake were especially observed to 1989. Resistant to the pollution macrophytes species began to dominate in the Lake. In 2007–2008 in the main part of the Lake, in which INPP sewage entered, only resistant to anthropogenic impacts macrophytes species were found. Fish species composition also has changed. The varietal diversity of the fish in the Lake significantly decreased from 23–26 (before INPP start-up) species to 14 ones. Considering the findings of our study, it can be assumed that changes in macrophytes species and fish varietal diversity in Drūkšiai Lake could be induced by total chemical, thermal and radioactive pollution, which had a negative impact on aquatic organisms. It can be predicted that new ecological conditions will appear in Drūkšiai Lake after INPP closing in 2009, notably after the changes of thermal water regime. However, the chemical and radioactive pollution in the Lake will be over a long period of INPP dismantling works. In addition, the great challenge for the ecosystem of Drūkšiai Lake will be a new nuclear power plant construction near the closed INPP.Article in English.Makrofitų ir žuvų rūšinė kaita drūkšių ežere – Ignalinos atominės elektrinės aušinimo baseine (1988–2008)Santrauka. Remiantis radionuklidų bei sunkiųjų metalų akumuliacijos ir sklaidos Drūkšių ežero biotiniuose ir abiotiniuose sanduose bei ilgalaikiais vandens ir dugno nuosėdų toksiškumo bei genotoksiškumo tyrimais, buvo įvertintas galimas radioaktyviosios, cheminės ir šiluminės taršos poveikis Drūkšių ežero makrofitams ir žuvims. Prieš pradedant veikti Ignalinos atominei elektrinei (IAE) buvo rasta 95 makrofitų rūšys. 1987 m. pradėjus veikti Ignalinos atominės elektrinės (IAE)antrajam energoblokui, ypač iki 1989m., nustatyta žymi makrofitų Drūkšių ežere rūšinės sudėties ir biomasės kaita. ėmė vyrauti taršos poveikiui atsparios makrofitų rūšys. 2007–2008 m. pagrindinėje ežero dalyje, į kurią patenka IAE nuotekos, rasta tik atsparios antropogeninių veiksnių poveikiui makrofitų rūšys, pasikeitė ir žuvų rūšinė sudėtis. Ežere žymiaisumažėjo žuvų rūšinė įvairovė: nuo 23–26 (prieš IAE paleidimą) iki 14 žuvų rūšių. Apibendrinant duomenis galima teigti,kad Drūkšių ežero augalijos ir gyvūnijos pokyčiai galėjo būti indukuoti suminės – cheminės, šiluminės ir radioaktyviosios taršos. Galima prognozuoti, kad uždarius IAE (2009-12-31.) Drūkšių ežere susiformuos naujos ekologinės sąlygos, ypač – pasikeitus terminiam vandens režimui, tačiau dugno nuosėdų cheminė ir radioaktyvioji tarša išliks. Per ilgą IAE išmontavimo periodą tarša gali dar padidėti. Be to, didelis išbandymas Drūkšių ežerui bus šalia uždarytos IAE numatoma naujos AE statyba.Reikšminiai žodžiai: Drūkšių ežeras, Ignalinos atominė elektrinė, radioaktyvioji, cheminė ir terminė tarša, vanduo, dugno nuosėdos, toksinis irgenotoksinis poveikis, makrofitai, žuvys.Изменение видового состава макрофитов и рыб воз. Друкшяй – водоеме охладителе Игналинской атомной электростанции (1988–2008 гг.)Резюме. На основании многолетних данных, полученных при изучении аккумуляции и миграции радионуклидов и тя желых металлов в биотических и абиотических компонентах озера Друкшяй, а также токсического и геноток сического действия воды и донных отложений на тесторганизмы, было оценено возможное действие теплового, химического и радиоактивного загрязнения на видовой состав макрофитов и рыб. До пуска Игналинской атомной электростанции (ИАЭС) в озере Друкшяй было установлено 95 видов макрофитов. В 1987 г. после пуска 2го энергоблока ИАЭС, особенно до 1989 г., в оз. Друкшяй было отмечено изменение видового состава и биомассы макрофитов. В озере стали бурно развиваться более устойчивые к действию антропогенных факторов среды виды макрофитов. В 2007–2008 гг. в основной части озера, в которую поступают сточные воды ИАЭС, были найдены лишь те виды макрофитов, которые наиболее устойчивы к действию различных загрязнителей. В озере также отмечено изменение видового состава рыб. Из 23–26 видов, установленных до пуска ИАЭС, осталось лишь 14 видов рыб. На основании полученных данных можно предположить, что изменения, происходящие в видовом составе макрофитов в оз. Друкшяй, были индуцированы совместным действием химического, теплового и радиоактивного факторов среды, которые могли представлять особую опасность и для других видов гидробионтов. Можно прогнозировать, что после закрытия ИАЭС в 2009 г. в оз. Друкшяй будут формироваться новые экологические условия, особенно связанные с изменениями термического режима воды. Однако химическое и радиоактивное загрязнение озера будет существовать долгие годы во время демонтирования ИАЭС. Кроме того,рядом с ИАЭС намечается строительство новой АЭС, что будет новым вызовом для оз. Друкшяй.Ключевые слова: озеро Друкшяй, ИАЭС, радиоактивное, химическое и термическое загрязнение, вода, донные осадки, токсическое и генотоксическое действие, макрофиты, рыбы.